A Prospective Assessment of Surgical Risk Factors in 114 Gluteal Fold Flap Reconstructions After Oncological Vulvoperineal Resection. Issue 1 (July 2017) - Lange, Maurits; Hage, J. Joris; van Beurden, Marc
Abstract : Background and Aim: To date, clinically relevant selection criteria have not been established for the use of the gluteal fold flap after oncological vulvoperineal resection. We prospectively assessed the surgical risk factors of this reconstructive technique in a large series. Methodology: From April of 2000 through December of 2015, 114 gluteal fold flaps were used for vulvoperineal reconstruction after excision of (pre)malignant skin disorders in 75 women. The possible influence of 10 patient-related and 6 procedure-related risk factors on flap-related postoperative complications was statistically analyzed. Results: We observed a major complication in 13 flaps (11%) and a minor complication in 19 flaps (17%). Previous radiotherapy ( P = 0.01) was associated with significantly more complications, and a rotation flap design rather than VY advancement ( P = 0.02) was associated with major complications. Recurrent disease, multifocal tumor localization, incomplete removal of tumor, and bilateral flap procedure were found to be clinically relevant risk factors, but not significantly so. The same applied to recurrence of disease during postoperative follow-up. Conclusions: We identified surgical risk factors for gluteal fold flap use after oncological vulvoperineal resection. These observations may potentially allow for more favorable future surgical outcomes by adaption of selection of patients or procedure.